2022
DOI: 10.1097/scs.0000000000008973
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Tissue Expansion: Analysis of the National Surgical Quality Improvement Program–Pediatric

Abstract: Introduction: Tissue expansion (TE) in pediatric surgery provides vascularized tissue to attain functional and esthetic goals in a broad range of reconstructive procedures. Our study evaluates the demographic, operative, and short-term outcomes of TE in pediatric patients utilizing the American College of Surgeons National Surgical Quality Improvement Program-Pediatric (NSQIP-P) database and highlights factors associated with postoperative complications. Materials and Methods: Retrospective review of a large m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Over a fifth of patients (21.4%) in this study cohort experienced SSI, while 17.9% had wound dehiscence. The rate of SSI reported in previous studies ranges from 4 to 9% 2,10,16–21,23,24,26,31 . Previous studies from Jeschke et al and Yeong et al showed that larger TBSA and deeper burns were associated with a greater risk of complications, including SSI 6,8,9 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Over a fifth of patients (21.4%) in this study cohort experienced SSI, while 17.9% had wound dehiscence. The rate of SSI reported in previous studies ranges from 4 to 9% 2,10,16–21,23,24,26,31 . Previous studies from Jeschke et al and Yeong et al showed that larger TBSA and deeper burns were associated with a greater risk of complications, including SSI 6,8,9 .…”
Section: Discussionmentioning
confidence: 94%
“…The rate of SSI reported in previous studies ranges from 4 to 9%. 2,10,[16][17][18][19][20][21]23,24,26,31 Previous studies from Jeschke et al and Yeong et al showed that larger TBSA and deeper burns were associated with a greater risk of complications, including SSI. 6,8,9 Similarly, this study showed a significant association between large TBSA, a higher number of TEs, and the likelihood of wound complications, including SSI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations